THE EFFECT OF BRAND EQUITY ON CONSUMER LOYALTY OF ESQA COSMETICS IN BANDAR LAMPUNG - Viola De Yusa; Andini Ira Maulina (Universitas Putera Batam, 2022)
The purpose of this study was to determine the effect of 1) Brand Awareness, 2) Brand Association, 3) Perceived Quality, 4) Brand Loyalty on ESQA cosmetic customer loyalty in Bandar Lampung. The population in this study were female customers who used ESQA cosmetic products in Bandar Lampung. The sample in this study were 80 respondents. The results of the study stated thatBrand Awareness(X1) Brand Association (X2), Preceived quality (X3), Brand Loyalty (X4) influence on Consumer Loyalty (Y) on ESQA Cosmetic Products in Bandar Lampung.